Comparison of Liver Function Tests in Normal Pregnancy with Non-pregnant Matched Controls (TAJ: Journal of Teachers Association, 2020)
Background: Change of liver biochemical profiles is normal during pregnancy. It is almost impossible to understand disease processes that can threaten women during pregnancy without understanding normal physiological change. Aim of this study is to evaluate changes in serum liver function tests in normal pregnant women in first, second and third trimester.Material and Methods: The cross-sectional comparative study was carried out in the Department of Obstetrics & Gynaecology of Rajshahi Medical College Hospital, Bangladesh in 2019. This study consists of 90 pregnant women and 90 matched control. Among the 90 pregnant women, 30 were in first trimester, 30 were in second trimester and 30 were in third trimester. Blood samples were taken for routine liver function and protein profilesResults: Serum total and direct bilirubin concentrations were significantly lower in second and third trimester. The mean ALP level was slightly increased in 2nd trimester and drastically increased in 3rd trimesters during pregnancy. Serum ALT and AST activity was significantly increased in third trimester. No significant change in serum total proteins concentration, but serum albumin concentration was significantly lower and serum globulin concentration was significantly higher in all three trimester. Serum albumin/globulin ratio was significantly reduced in second and third trimester.Conclusion: Relative values of various liver function tests during gestational trimesters appear to be the best guide to confirm the diagnosis and treatment strategies. Thus, gynecologists should routinely monitor liver function tests in all gestational trimesters to avoid the future complications to mother and offspring.TAJ 2020; 33(1): 17-24